Filosofi Manajemen Pendidikan Islam dalam Perspektif Al-Qur'an - Mira Marisa (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2021)
Humans are creatures who have a great sense of curiosity. In its history, humans are creatures who do not stop to philosophize, which in essence is that human beings will always seek a truth. Especially how humans are able to manage their own thoughts. relating to humans who will not be separated from the problem of their thinking, this is related to the study of philosophy. Study of philosophy or philosophy in which it connects scientific terms, such as ontology, epistemology and axiology. Of course this is a conversation in which in the three terms, the three of them have different opinions regarding truth research. For this reason, with his thoughts, humans are expected to be able to study various perspectives on scientific research. This research uses library research method, namely library research. With data collection techniques based on reading and writing results from several references such as books, journals and so on. Science from time to time will continue to carry out civilization. It can be seen clearly how the developing field of science gives rise to a plan and movement with the goals to be achieved. The field of science in question is the management of Islamic education. In the perspective of the Al-Qur’an, the management of Islamic education is related to how the forms of cooperation in managing and carrying out tasks in an institution are in line with an Islamic view